Effect of shading net, planting methods and bio-extract on production of muskmelon - Abdulraheem. A. Obaid; Hassan H. Al-Alawy; Kadhum Daley Hassan; Ghassan Jaafar Hamdi (Agraarteadus, 2021)

(untitled)
Growing vegetable transplants under shade nets are currently becoming more popular to protect high intensities of light and high temperature. This study was undertaken to evaluate the influence of shading net at 30% shading and an unshaded control, methods of the planting, direct sowing, transplanting, and foliar application of a biozyme fertilizer at 0 and 0.5 ml L–1 production, and quality of muskmelon. These treatments were laid out in a randomized complete block design (RCBD) and were arranged in a split‑split plot with three replications. Results showed that 30% shading treatment produced the highest leaf chlorophyll content (57.07 SPAD) and TSS (13.05%). Direct sowing gives a higher value for fruit weight (3583 g), most yield per plant (3772 g) and most total yield (3772 g). Transplanting produced the highest fruit per plant (1.58 fruit). The 0.5 ml L–1 fertilizer treatment had the least time to maturity (92.08 days). The interaction between shading treatment, establishment methods and biozyme fertilizer improve the fruit quality and yield of muskmelon.